USE OF GROWTH MODELS TO PREDICT THE BODY WEIGHT OF FUNAAB ALPHA (FÎ±) BROILER, ITS CROSSBREDS AND TWO OTHER EXOTIC BROILER CHICKENS AT EARLY STAGE OF GROWTH - Ogunpaimo, Olaiwola; Wheto, Mathew; Ojoawo, Henry; Adebambo, Ayotunde; Adebambo, Olufunmilayo; Durosaro, Samuel (FUDMA JOURNAL OF SCIENCES, 2020)
Body weight is one of the most important phenotypic parameters in poultry production as heavy meat birds attract good market value compare to their light breed counterpart. of chicken at the early stage of growth in order to assist the poultry farmers during the rearing stage. A total of 300 Oba Marshall, 300 Arbor Acre, 300 FÎ± broiler, 300 FÎ± X Ms, 300 FÎ± X AB, 300 Ms X FÎ± and 300 AB X FÎ± crossbred chicks of both sexes were used to evaluate variations in the body weight of FÎ± broiler, its crossbreds and two other exotic chickens using Gompertz and Von Bertalanffy growth models.  Body weights of the chicks were taken on weekly basis using sensitive weighing balance till they attained 10 weeks of age. The two Non-Linear Models were fitted to the weight-age data from day old till 10 weeks of age for each bird using â€˜Doesnâ€™t Use Derivative method of SAS (2002) to estimate parameters of all the models in order to predict the weight of the birds at early stage. Results revealed that body weight was influenced (P
Keywords: FUNAAB-Alpha; Gompertz; Von Bertalanffy growth model